2005
DOI: 10.1002/uog.1930
|View full text |Cite
|
Sign up to set email alerts
|

Posterior compartment prolapse on two-dimensional and three-dimensional pelvic floor ultrasound: the distinction between true rectocele, perineal hypermobility and enterocele

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
143
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 13 publications
2
143
1
6
Order By: Relevance
“…Thus, while some reports have correlated pelvic floor abnormalities with obstetric trauma (4,10,12,23) , others have failed to identify an association between the incidence of such dysfunctions and vaginal delivery (17,20,27) . According to Dietz et al (6,7) true rectocele is a rectovaginal septum defect in younger nulliparous women, the prevalence and size of which appear to be associated with childbirth. Regadas et al (21) clearly demonstrated gender-specific differences in anal canal anatomy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, while some reports have correlated pelvic floor abnormalities with obstetric trauma (4,10,12,23) , others have failed to identify an association between the incidence of such dysfunctions and vaginal delivery (17,20,27) . According to Dietz et al (6,7) true rectocele is a rectovaginal septum defect in younger nulliparous women, the prevalence and size of which appear to be associated with childbirth. Regadas et al (21) clearly demonstrated gender-specific differences in anal canal anatomy.…”
Section: Resultsmentioning
confidence: 99%
“…Different techniques and imaging methods have been used to evaluate pelvic floor dysfunctions in the anterior, middle and posterior compartment (2,3,7,8,9,12,14,15,16,17,18,19,20,24,25,27) . Because of differences in measurement techniques and anatomical landmarks, some authors describe rectocele as a descent of the rectal ampulla, quantified by correlation with the inferoposterior margin of the symphysis pubis (8,12) , while others consider rectocele a herniation of the anterior rectal wall into the posterior vagina, the size of which determines the grade of rectocele (2,3,9,13,15,17,19,20,23,27,29) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TLUS provides two-dimensional (2D) imaging of the pelvic floor. In the midsagittal plane, all anatomical structures (bladder, urethra, vaginal walls, anal canal and rectum) between the posterior surface of the symphysis pubis and the posterior part of the levator ani are visualized [7]. …”
mentioning
confidence: 99%
“…This dynamic modality allows assessment of pelvic organ prolapse, perineal descent or pelvic floor dyssynergy. Using 3D volumetric probes developed for obstetric imaging, 3D-and 4D-TLUS may be performed [7]. An advantage of this technique, compared with 2D mode, is the opportunity to obtain tomographic or multislice imaging, for example in the axial plane, in order to assess the entire puborectalis muscle and its attachment to the pubic rami.…”
mentioning
confidence: 99%